Implementasi Program Revitalisasi Pojok Baca dan Perpustakaan sebagai Upaya Meningkatkan Minat Baca Siswa SDN Wonoayu - Aprilia, Nesa Dwi; Nugraha, Rama Fanie; Astuti, Bela Puji; Nadif, Difa Layla; Prasetya, Ahmad Dwi Nur (Indo-MathEdu Intellectuals Journal, 2026)
The low interest in reading among students is caused by the condition of the reading corner and library which are poorly organized and less attractive. This study aims to describe the implementation of the reading corner and library revitalization program as an effort to increase students' interest in reading at SDN Wonoayu. The method used is a qualitative descriptive study carried out by KKN-T Group 15 students from Universitas PGRI Madiun involving SDN Wonoayu school residents. Data collection techniques include observation, interviews, and documentation. Furthermore, the data were analyzed using content analysis techniques through the process of data reduction, data presentation, and drawing conclusions. The results of the study show that after the revitalization program was implemented, there was an increase in students' interest in reading, marked by increased use of the reading corner and library by students, especially during breaks and learning activities. This revitalization creates a comfortable, neat, and attractive reading environment that encourages students to read independently. Thus, the reading corner and library revitalization program plays an important role in supporting literacy activities and fostering a culture of reading in elementary schools.